Impact of calcium lactate and polysaccharides on skim milk gelation : a thesis presented in partial fulfilment of the requirements for the degree of Master in Food Technology at Massey University, Albany, New Zealand - Cao, Zheming (Alcoli) (Massey University, 2020)
Swallowing difficulty is a growing health issue in adults particularly in the elderly population throughout the world. Thickeners and/or stabilisers are often added to the fluids to make them easier to swallow. Calcium-fortified dairy products have also been recommended for adults and the elderly to minimise the development of osteoporosis. Texture-modified milk with added calcium and polysaccharides could benefit adults who require an adequate calcium intake and have swallowing difficulties. Therefore, this project aimed to investigate the effect of the addition of calcium lactate to skim milk with and without polysaccharides. This project examined the calcium-added skim milk with and without polysaccharides for physical and rheological properties and microstructure. The first part of this project studied the effect of different heat treatments and the addition of different concentrations of calcium lactate on skim milk. The skim milk samples with added calcium lactate were heat treated at different temperatures (65°C, 70°C, 75°C and 80°C) and held at different periods of time (30 min or 60 min), followed by cooling to 20°C. The second part of this project investigated the effect of the addition of calcium lactate and three polysaccharides (xanthan gum, high acyl gellan gum and guar gum) on skim milk with calcium lactate after heating and holding at 75°C for 30 min. The physical properties of the skim milk samples were visually examined after heat treatment and the rheological properties were determined for different concentrations of polysaccharides using a rheometer. The microstructure of the samples was studied using a scanning electron microscope (SEM). Increasing the concentration of calcium lactate promoted the gelation of skim milk along with high heating temperatures (>70°C) and longer holding times. At the concentrations <10mM added calcium lactate, liquid skim milk samples with no gelation were observed. When the concentration of added calcium lactate was greater than 10mM, hard and firm gels were formed at all heat treatments. The final G’ increased with increasing concentration of added calcium lactate and higher heating temperature and longer holding times. The highest final G’ was achieved when the sample with 20mM added calcium lactate was heated at 80°C for 60 min. The addition of xanthan gum, high acyl gellan gum or guar gum demonstrated different interactions with calcium lactate in the milk system. At 10mM and 15mM calcium lactate, soft gels were formed when the xanthan concentration was less than 0.2% and viscous liquids were formed and became more viscous as the xanthan gum concentration increased above 0.2%. A dense and compact network with crosslinking was observed under SEM when 0.3% xanthan gum and 15mM calcium lactate were added to skim milk. With the addition of high acyl gellan gum, firmer gels were formed and the final 𝘎’ with increasing concentration of high acyl gellan gum, while a fibrous network was observed at 0.3% added high acyl gellan gum. With the addition of guar gum, soft gels were produced with aggregates and phase separation was observed when 0.2%-0.3% guar gum was added. The final 𝘎’ did not increase significantly (p<0.05) as the concentration of guar gum increased and a less compact structure was observed under SEM. The major findings in this study may be used as a guideline for the potential development of thickened milk beverages. The mouthfeel of the skim milk with 10mM and 15mM calcium lactate was improved when the xanthan concentration increased above 0.1% and a smooth mouthfeel was perceived at 0.5% added xanthan. Guar gum was not recommended to be used as undesirable mouthfeel was perceived.
Figures 2.1 (=Horne, 2006 Fig 1) & 2.6 (=Loren et al., 2007, Fig 9.3) were removed for copyright reasons.
Keywords: 400405 Food engineering